2013
DOI: 10.1136/bcr-2013-202196
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury as first presentation of lymphoma: the role of renal biopsy

Abstract: A 65-year-old man with an insidious history of being generally unwell with weight loss, a poor appetite and night sweats was transferred to a tertiary nephrology unit after being found to be in acute kidney injury (AKI). A renal biopsy was performed on the same day which revealed lymphomatous infiltration of the renal parenchyma. He required temporary haemodialysis as he was oliguric and was started on chemotherapy. His renal function improved to baseline 3 weeks after treatment. This case illustrates the unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…There are some case reports, illustrating kidney pathology of AKI in lymphomas, and demonstrating LI in one case and light chain cast-nephropathy in another. 18,19 In the study from China kidney biopsy was performed in 18 out of 20 patients with NHL, only 5 of them presented with AKI, and in these patients pathology showed MPGN, intraglomerular lymphoma and intracapillary monoclonal IgM deposits. 20 Study of 49 patients with CLL and monoclonal B-cell lymphocytosis from Mayo clinic 16 reports renal failure (without distinguishing acute or chronic) in 34 (69%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…There are some case reports, illustrating kidney pathology of AKI in lymphomas, and demonstrating LI in one case and light chain cast-nephropathy in another. 18,19 In the study from China kidney biopsy was performed in 18 out of 20 patients with NHL, only 5 of them presented with AKI, and in these patients pathology showed MPGN, intraglomerular lymphoma and intracapillary monoclonal IgM deposits. 20 Study of 49 patients with CLL and monoclonal B-cell lymphocytosis from Mayo clinic 16 reports renal failure (without distinguishing acute or chronic) in 34 (69%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Several case series from autopsies performed in patients who had lymphoma show that the presence of malignant lymphocytes in the kidneys may occur more commonly than clinically suspected 6–10. One small case series demonstrated that while 14% of patients had been diagnosed with renal infiltration by their lymphoma, autopsies showed that there were actually 34% of patients with renal involvement 10.…”
Section: Discussionmentioning
confidence: 99%
“…This under diagnosis is likely due to most patients lacking clear clinical and/or radiological findings of renal lymphocytic invasion 8 9. However, clinically relevant renal involvement in low grade B-cell lymphoproliferative malignancies does remain rare 1–4 7 11–24…”
Section: Discussionmentioning
confidence: 99%